INTEGRATING SOFT SKILLS INTO A TEACHER EDUCATION CURRICULUM - STEPHEN MAREN, MACQUAL,; SALLEH, UMI KALSUM MOHD.; ZULNAIDI, HUTKEMRI (International Journal of Psychosocial Rehabilitation, 2024)
Recent developments suggest that soon, soft skillsare likely to become moreimportant in sustaining teachers duringteaching. This study looks at pre-service teachers’ soft skills gained from participation insoft skillscourses that are compulsory second- and third-year undergraduate teacher education course designed to equip preservice teachers with sustainablesoft skills.We grounded our study on acceptance and commitment training, and social change modelto examine the extent soft skills can be effectively fostered in teachereducation.We used paper questionnaires and performed data analysis usingSPSS and SmartPLS software in aquasi-experimental procedure with a population of 722 pre-service teachers.In all semesters scores on the soft skills scales showed significant improvement over the course of the semester, with moderate to large positive effect. Experienced and novice pre-service teachers were compared. Importantly, it was found that the effect of the course fostering was successful across participants as analysis did not show any significant difference between the participants in the soft skills self-rated scales. Partial least square structural equation modelling analysis revealed interestinglythat all the pre-service teachers gained soft skills in levels that were both moderate and significant.Implying the strength of the soft skills curriculum and the credit-hours allocated must be examined.